1995
DOI: 10.1002/j.1460-2075.1995.tb00091.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel iron uptake mechanism mediated by GPI-anchored human p97.

Abstract: The established process for iron uptake into mammalian cells involves transferrin and its receptor. Here, the role of the glycosyl‐phosphatidylinositol (GPI)‐linked transferrin homologue, melanotransferrin or p97, was studied using CHO cell lines defective in the transferrin receptor (TR) and transfected with human TR and/or human p97. The presence of p97 doubled the iron uptake, which could be explained by the binding of one atom of iron to one molecule of p97. The internalization of iron was shown to be temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
76
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 58 publications
7
76
1
Order By: Relevance
“…These CHO cells expressed 1.2 Â 10 6 MTf molecules per cell, a level three-to four-fold higher than that of the most highly expressing, naturally-derived melanoma cell line, SK-MEL-28 (300-380 000 sites/cell; Brown et al, 1981a;Sekyere and Richardson, 2000). However, after an incubation of 240 min, the Fe uptake from 59 Fe-citrate was only 2.4 times greater than the control CHO cells not expressing MTf (Kennard et al, 1995). Furthermore, hyper-expression of MTf did not result in any increase in Fe uptake from Tf when compared with control cells (Kennard et al, 1995).…”
Section: Functional Role Of Mtf: Melanoma Iron Transport and Metabolismmentioning
confidence: 96%
See 2 more Smart Citations
“…These CHO cells expressed 1.2 Â 10 6 MTf molecules per cell, a level three-to four-fold higher than that of the most highly expressing, naturally-derived melanoma cell line, SK-MEL-28 (300-380 000 sites/cell; Brown et al, 1981a;Sekyere and Richardson, 2000). However, after an incubation of 240 min, the Fe uptake from 59 Fe-citrate was only 2.4 times greater than the control CHO cells not expressing MTf (Kennard et al, 1995). Furthermore, hyper-expression of MTf did not result in any increase in Fe uptake from Tf when compared with control cells (Kennard et al, 1995).…”
Section: Functional Role Of Mtf: Melanoma Iron Transport and Metabolismmentioning
confidence: 96%
“…It is of interest to note that Kennard et al (1995) showed that MTf-transfected Chinese hamster ovary (CHO) cells could internalize Fe from Fe(III) citrate complexes. These CHO cells expressed 1.2 Â 10 6 MTf molecules per cell, a level three-to four-fold higher than that of the most highly expressing, naturally-derived melanoma cell line, SK-MEL-28 (300-380 000 sites/cell; Brown et al, 1981a;Sekyere and Richardson, 2000).…”
Section: Functional Role Of Mtf: Melanoma Iron Transport and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Other mechanisms may be involved in Fe acquisition from transferrin by some cell types (17)(18)(19)(20)(21)(22)(23)(24). In most studies the mechanism responsible remains ill defined.…”
mentioning
confidence: 99%
“…However, a pathway involving the intracellular protein mobilferrin in conjunction with membrane integrins has been described (21,22). Melanotransferrin, a plasma membrane-associated Fe-binding protein in human melanoma and other cell lines, has also been implicated in some forms of Fe acquisition from transferrin (23,24). These processes do not appear to require transferrin internalization.…”
mentioning
confidence: 99%